PEMBENTUKAN NILAI-NILAI KARAKTER PESERTA DIDIK SMAN 4 PANGKEP DI LINGKUNGAN KELUARGA PADA MASA PANDEMI COVID-19 - Nurmaulidiyah Al-Mubakkirah; Hasnawi Haris; Muataring Mustaring (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2021)
The purpose of this research; 1) To find out the process of forming character values ​​for students during the pandemic in the family environment of SMAN 4 Pangkep, 2) To find out the character of SMAN 4 Pangkep students during the pandemic. This type of research is qualitative research using a descriptive approach. Data collection techniques include: observation, interviews and documentation. The data obtained from the research results were processed using descriptive qualitative data analysis. The results showed that (1) The process of forming character values ​​for students at SMAN 4 Pangkep in the family environment during the pandemic went through the knowledge stage such as giving advice, the implementation stage included inviting students, and the habituation stage including sanctioning (2) Character students of SMAN 4 Pangkep during the pandemic, the religious character of the students' character is getting better due to parental supervision, in the disciplined character some of the student's characters are decreasing because during the pandemic period students sometimes don't do assignments and don't even follow the learning process. In honest character, the character of students also decreases because students are easier to cheat, and are easier to lie.